Isolation and characterization of antifungal compounds from Clerodendron glabrum var glabrum (Verbenaceae) used traditionally to treat candidiasis in Venda, South Africa - Eloff, Jacobus Nicolaas (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.